IMPROVING THE EFFICIENT USE OF STATE FINANCIAL PECUPCLAP IN PROVIDING EMPLOYMENT OF THE POPULATION - PhD., Abduraimova Nigora Radjabovna (Scholar Express Journals, 2024)
According to scientific research, there is a certain category of people who are experiencing certain difficulties in the labor market. Including: young and old workers; demobilized medical officer; long-term employment; certain people who do not want to work, huchucan, nogiponlap, and young people who have never studied and do not work.
Keywords: state budget revenues; GDP